The impact of using Binahong (Anredera Cardifolia) leaf extract on male wistar white rats fed a high-fat diet's liver function and liver histopathology - Kusumawardhany, Fitria Marizka; Hanjaya, Hanjaya; Samin, Buter (Science Midwifery, 2024)
Worldwide, Nonalcoholic Fatty Liver Disease (NAFLD) is the leading cause of chronic liver disease. Nutritional excess causes adipose depot enlargement and ectopic fat buildup, causing NAFLD. The Binahong plant (Anredera cordifolia) contains saponins, alkaloids, polyphenols, flavonoids, and mono polysaccharides like L-arabinose, D-galactose, L-rhamnose, and D-glucose, which have been shown to help NAFLD. The study examined the liver function and histopathology of male white Wistar rats fed high-fat diets after Binahong leaf extract was administered. Research approach/sample/population: Quantitative research employing lab or experiment formats. We sampled 24 white Wistar rats (Rattus norvegicus). A high-fat diet was the precondition, Binahong leaf extract was the independent variable, and liver function and histological characteristics improved. The research approach begins with test animal acclimation, Binahong leaf extract extraction, phytochemical screening, treatment protocols, examination, and Histopathology preparations. Research data was processed with SPSS. The normality test shows a 2-tailed significance of 0.678 > 0.05, indicating regularly distributed data. SGOT 0.10 and SGPT 0.20 liver function analyses demonstrated homogeneity p values > 0.05. The research found that Binahong leaf extract (Anrederacordifolia Ten. Steenis) has 400mg/BW antioxidants and can restore liver function in high-fat livers.